Academic Stress Among Nursing Students: A Descriptive Cross-Sectional Study - Mankoo, Anjali (Journal of Social Science and Humanities, 2025)
Background: Stress, we’ve all felt it. Sometimes stress can be a positive force, motivatingyou to perform well at your piano recital or job interview. But often, like when you’re stuck in traffic, it’s a negative force. If you experience stress over a prolonged period, it could become chronic, unless you take action1 The present study aimed to assess the academic stress among Nursing Students at SIPS Pvt.Ltd, Lucknow. Methods: In this study, a descriptive research design and non-probability purposive samplingtechnique were used. A total of 110 samples were selected. The perceived stress scale was used to assess stress. Results: The result revealed that among all 110 participants, with academic courses BSc Nursing, GNM, ANM, and Paramedical. And age group of students were 17-25 above 27(24.5%) had low stress,56 (50.9%) had moderate stress levels of knowledge, and (24.5%) had high perceived stress levels. The mean score of participants was 20.98 and the SD was +_8.15. Significant association was found only with marital status, residence, and residence during education. Conclusions: The study concluded that there was a moderate level of academic stress from areas of workload, and assignments, that is why there is a need for stress-relieving exercises/therapies for all students suffering from stress.